The Office of SUARA UMP donates 63 books to UMP library - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2020)
Pekan, 26 August 2020 - The office of SUARA UMP donated 63 books published in-house to the UMP Library to elevate the momentum of the National Day celebration in conjunction with the 63rd independence.